Component‐resolved diagnosis and beyond: Multivariable regression models to predict severity of hazelnut allergy. Issue 3 (24th November 2017) - Datema, M. R.; van Ree, R.; Asero, R.; Barreales, L.; Belohlavkova, S.; de Blay, F.; Clausen, M.; Dubakiene, R.; Fernández‐Perez, C.; Fritsche, P.; Gislason, D.; Hoffmann‐Sommergruber, K.; et al.
Abstract: Background: Component‐resolved diagnosis (CRD) has revealed significant associations between IgE against individual allergens and severity of hazelnut allergy. Less attention has been given to combining them with clinical factors in predicting severity. Aim: To analyze associations between severity and sensitization patterns, patient characteristics and clinical history, and to develop models to improve predictive accuracy. Methods: Patients reporting hazelnut allergy (n = 423) from 12 European cities were tested for IgE against individual hazelnut allergens. Symptoms (reported and during Double‐blind placebo‐controlled food challenge [DBPCFC]) were categorized in mild, moderate, and severe. Multiple regression models to predict severity were generated from clinical factors and sensitization patterns (CRD‐ and extract‐based). Odds ratios (ORs) and areas under receiver‐operating characteristic (ROC) curves (AUCs) were used to evaluate their predictive value. Results: Cor a 9 and 14 were positively (OR 10.5 and 10.1, respectively), and Cor a 1 negatively (OR 0.14) associated with severe symptoms during DBPCFC, with AUCs of 0.70‐073. Combining Cor a 1 and 9 improved this to 0.76. A model using a combination of atopic dermatitis (risk), pollen allergy (protection), IgE against Cor a 14 (risk) and walnut (risk) increased the AUC to 0.91. At 92% sensitivity, the specificity was 76.3%, and the positive and negative predictive values 62.2% and 95.7%, respectively. For reported symptoms, associations and generated models proved to be almost identical but weaker. Conclusion: A model combining CRD with clinical background and extract‐based serology is superior to CRD alone in assessing the risk of severe reactions to hazelnut, particular in ruling out severe reactions.